MARKETING CHANGES MANAGEMENT - T. D. Maslova; S. G. Bozhuk; D. V. Smirnova (Дискурс, 2019)
The article considers the categories of "transformation" and "development" as the transition of economic entities from one qualitative state to another. The role and place of marketing planning in business activity is demonstrated. Marketing planning is considered the most important function of marketing management in the situation that is constantly changing. The authors define the notions of "marketing changes" and "marketing planning" and reveal the insights into the concepts. The algorithm of marketing planning process is developed, and its stages are reviewed. The place of marketing planning in the functions of marketing management is determined at different levels. It allows to respond to changes promptly and correctly. Marketing changes are specified. They are classified according to the power of influence and the extent of adjustments of the marketing plan.